Synthesis, structure and dynamics of a c2-symmetrical bis(oxazolinylmethylene)pyrrolinato-zinc complex - Capacchione, Carmine; Wadepohl, Hubert; Gade, Lutz H. (Zeitschrift für anorganische und allgemeine Chemie, 2007)
Reaction of 2,5-bis(cyanomethyl)pyrrole with L-valinol in presence of zinc trifluoromethansulfonate and subsequent work-up with aqueous NaCl gave the corresponding zinc complex 2, in which the double bonds of the pyrrole ring isomerize to give rise to a conjugated chromophore. Its molecular structure displays tetrahedral distortion from planarity, as was established by a single crystal structure analysis. The non-planarity of 2 gives rise to a dynamic behaviour in solution with the chlorido-ligand swinging through the plane spanned by the three N-donor functions.